Anticoagulation in patients with atrial fibrillation and active cancer: an international survey on patient management. (3rd September 2020) - Boriani, Giuseppe; Lee, Geraldine; Parrini, Iris; Lopez-Fernandez, Teresa; Lyon, Alexander R; Suter, Thomas; Van der Meer, Peter; Cardinale, Daniela; Lancellotti, Patrizio; Zamorano, Jose Luis; Bax, Jeroen J; Asteggiano, Riccardo; et al.
Abstract: Background: In patients with active cancer and atrial fibrillation (AF) anticoagulation, thrombotic and bleeding risk still entail uncertainty. Aim: We explored the results of an international survey examining the knowledge and behaviours of a large group of physicians. Methods and results: A web-based survey was completed by 960 physicians (82.4% cardiologists, 75.5% from Europe). Among the currently available anticoagulants for stroke prevention in patients with active cancer, direct oral anticoagulants (DOACs) were preferred by 62.6%, with lower values for low molecular weight heparin (LMWH) (24.1%) and for warfarin (only 7.3%). About 46% of respondents considered that DOACs should be used in all types of cancers except in non-operable gastrointestinal cancers. The lack of controlled studies on bleeding risk (33.5% of respondents) and the risk of drug interactions (31.5%) were perceived as problematic issues associated with use of anticoagulants in cancer. The decision on anticoagulation involved a cardiologist in 27.8% of cases, a cardiologist and an oncologist in 41.1%, and a team approach in 21.6%. The patient also was involved in decision-making, according to ∼60% of the respondents. For risk stratification, use of CHA2 DS2 -VASc and HAS-BLED scores was considered appropriate, although not specifically validated in cancer patients, by 66.7% and 56.4%, respectively. Conclusion: This survey highlights that management of anticoagulation in patients with AF and active cancer is challenging, with substantial heterogeneity in therapeutic choices. Direct oral anticoagulants seems having an emerging role but still the use of LMWH remains substantial, despite the absence of long-term data on thromboprophylaxis in AF.